2011
DOI: 10.1177/039463201102400225
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated Imiquimod Application Site Reactions in the Context of Systemic Tumor Necrosis Factor-Alpha Inhibition: More Than a Coincidental Occurrence?

Abstract: Topical imiquimod and tumor necrosis factor (TNF)-α inhibitors have gained wide acceptance as safe and effective treatments for non-melanoma skin cancer (NMSC) and moderate to severe psoriasis, respectively. While mild to moderate application site reactions (ASRs) are a well-known and common phenomenon associated with imiquimod, the potential of TNF-α blockers to elicit cutaneous inflammatory reactions has only recently been recognized. We present two cases of severe, atypical ASRs which occurred during NMSC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A high level of IL-6 gene was reported in the brain of autistic patients [60] . Besides, other authors established that numerous cytokines including IL-6 and IL-8 are raised in the plasma of young children with ASD and these rises are connected with more impaired communication and abnormal performances [61,62,63] .…”
Section: Discussionmentioning
confidence: 99%
“…A high level of IL-6 gene was reported in the brain of autistic patients [60] . Besides, other authors established that numerous cytokines including IL-6 and IL-8 are raised in the plasma of young children with ASD and these rises are connected with more impaired communication and abnormal performances [61,62,63] .…”
Section: Discussionmentioning
confidence: 99%
“…Imiquimod-induced psoriasis has sometimes been described in adult patients with a prior history of psoriasis (1,8). Moreover, there have been a few reports in children (2).…”
Section: Imiquimod-induced Psoriatic Erythroderma Treated With Inflixmentioning
confidence: 99%
“…In most previous studies, the symptoms were resolved by only application of topical calcipotriol or topical steroids and/or ultraviolet B treatment (1, 2). There have been 2 reports of treatment with infliximab, a chimeric monoclonal antibody against TNF-α, in the course of imiquimod-induced psoriasis, because of a flare of the patient's skin condition and complication of arthritis (8). However, the patients had pre-existing psoriasis, and new lesions developed at the site of imiquimod administration.…”
Section: Imiquimod-induced Psoriatic Erythroderma Treated With Inflixmentioning
confidence: 99%
“…Other authors reported that increased proinflammatory cytokine levels in the brain (TNF-a, IFN-y, IL-l~and IL-8); and NF-kappaB, may also contribute to autism spectrum disorders (24)(25)(26)(27). In addition, other authors confirmed that several cytokines and chemokines, including IL-l~, IL-6, IL-8 and IL-12p40, are elevated in the ASD plasma of very young children (ages 2-5 years old), and that these increases are associated with more impaired communication and aberrant behaviors (28)(29)(30)(31).…”
mentioning
confidence: 90%